2016
DOI: 10.18632/oncoscience.280
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the methylation cycle in cells reprogrammed into a stem cell-like state

Abstract: Generation of induced pluripotent stem (iPS) cells and cancer biogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 51 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Homocysteine is nonprotein amino acid which behaves as both a substrate and product of methionine. Homocysteine has key role in methylation cycle, within which a methyl group is transferred to a different substrate (Fernández-Arroyo et al 2016). Formed homocysteine can be utilized in two ways: 1) homocysteine can be remethylated to methionine by catalytic activity of the enzyme N5, N10-methylenetetrahydrofolate reductase; 2) homocysteine can be converted to D r a f t transformed into S-adenosylhomocysteine (SAH).…”
mentioning
confidence: 99%
“…Homocysteine is nonprotein amino acid which behaves as both a substrate and product of methionine. Homocysteine has key role in methylation cycle, within which a methyl group is transferred to a different substrate (Fernández-Arroyo et al 2016). Formed homocysteine can be utilized in two ways: 1) homocysteine can be remethylated to methionine by catalytic activity of the enzyme N5, N10-methylenetetrahydrofolate reductase; 2) homocysteine can be converted to D r a f t transformed into S-adenosylhomocysteine (SAH).…”
mentioning
confidence: 99%
“…The former hypothesis, formulated previously [ 75 ], was corroborated in our experiment by the tendency for greater mRNA abundance of MAT1A and PEMT ( P value < 0.10; Table 7 ) in MET calves. These genes, indeed, play an important role in hepatic phosphatidylcholine (PC) synthesis [ 76 78 ], which is known to participate in VLDL synthesis and help prevent fatty liver [ 79 , 80 ]. Endogenous synthesis of PC from supplemental Met [ 81 ] was already proposed to play a role in the ability of the cow liver to handle influx of FA produced from lipolysis after parturition [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…IDH2 was more abundant in WT MEFs than in KO and is responsible for the production of NADPH, whereas NADPH is essential for the proliferation of both normal and tumor cells 52 . In addition, NADPH is needed to establish cancer-like glycolytic phenotypes, which is further required for establishing and maintaining a DNA methylation pattern in iPSCs resembling that of ESCs 53 . Recently, it was reported that primed human pluripotent stem cells require SIRT2 downregulation to maintain pluripotency via altering metabolic pathways toward aerobic glycolysis 24 .…”
Section: Discussionmentioning
confidence: 99%